'Adults don't understand': exploring how teens use dialectical frameworks to navigate webs of tensions in online life. Issue 1 (1st January 2017) - Malvini Redden, Shawna; Way, Amy K.
ABSTRACT: As communication increasingly takes place online and via mobile technologies, young people are the fastest growing adopters of new online platforms. Consequently, communication scholars have begun to consider young people's experiences online, comparing online and offline interactions, establishing how developmental stages affect youth's engagement with online content, and documenting risks for youth's experience online. We argue that much can be gained from a 'tension-centered' approach that highlights the competing demands of young people's online engagement and problematizes current conceptions of risk. Through focus group interviews with teens, we examine current trends of online activity and re-conceptualize opportunities for conducting research with youth. Teens' 'local logics' for negotiation webs of communicative tensions online reveal articulation of formal rules, which are later eclipsed by lived experiences. We offer strategies for parents, caregivers, and educators to more productively engage with youth about their online experiences, as well as implications for communication researchers.